2003
DOI: 10.1128/jvi.77.19.10394-10403.2003
|View full text |Cite
|
Sign up to set email alerts
|

An Alphavirus Replicon Particle Chimera Derived from Venezuelan Equine Encephalitis and Sindbis Viruses Is a Potent Gene-Based Vaccine Delivery Vector

Abstract: Alphavirus replicon particle-based vaccine vectors derived from Sindbis virus (SIN), Semliki Forest virus,and Venezuelan equine encephalitis virus (VEE) have been shown to induce robust antigen-specific cellular, humoral, and mucosal immune responses in many animal models of infectious disease and cancer. However, since little is known about the relative potencies among these different vectors, we compared the immunogenicity of replicon particle vectors derived from two very different parental alphaviruses, VE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
165
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 162 publications
(169 citation statements)
references
References 63 publications
1
165
0
3
Order By: Relevance
“…Viral replicon particles (VRPs) were generated in baby hamster kidney (BHK) cells as previously described (14). Ag-expressing (or reporter geneexpressing) replicons derived from the Venezuelan equine encephalitis virus genome containing the 39 untranslated region and packaging signal of Sindbis virus (SV) were electroporated into BHK cells along with defective helper RNAs encoding the SV capsid and glycoprotein genes (10).…”
Section: Vaccine Groupsmentioning
confidence: 99%
“…Viral replicon particles (VRPs) were generated in baby hamster kidney (BHK) cells as previously described (14). Ag-expressing (or reporter geneexpressing) replicons derived from the Venezuelan equine encephalitis virus genome containing the 39 untranslated region and packaging signal of Sindbis virus (SV) were electroporated into BHK cells along with defective helper RNAs encoding the SV capsid and glycoprotein genes (10).…”
Section: Vaccine Groupsmentioning
confidence: 99%
“…For these studies, we used a self-amplifying RNA based on an alphavirus genome (10), which contains the genes encoding the alphavirus RNA replication machinery, but lacks the genes encoding the viral structural proteins required to make an infectious alphavirus particle (Fig. 1A).…”
mentioning
confidence: 99%
“…Indeed, in the case of SFV/HIV CAT , the presence of an SFV capsid protein would be expected to allow selectivity in viral genome packaging in SFV/ HIV CAT particles, even though several evidence has suggested that, besides the specific interaction of the alphavirus capsid with packaging signals, some other mechanism(s) might be involved in RNA packaging. 42,43 One important consideration might be the effect of the SFV/HIV CAT vector expression level in the co-transduced cells. However, even though the expression of the SFV/HIV CAT vector in transfected cells was not particularly high, efficient transducing ability of SFV/HIV CAT particles was achieved.…”
Section: Sfv/hiv Hybrid Vectors C Del Vecchio Et Almentioning
confidence: 99%